The Odd Squad : bully bait / 1. - Fry, Michael, 1959- (Odd Squad, 2013)
When his school counselor insists that he needs better socialization skills after being stuffed into a locker by a bully, middle-schooler Nick finds himself, along with two other misfits, joining the school's lamest club: Safety Patrol.